VARIABILITY OF PHYSICAL AND CHEMICAL PROPERTIES OF MAGNETITE AND QUARTZ OF THE NORTHERN DISTRICT OF KRYVYI RIH BASIN - Тіkhlivets S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Physical properties of minerals represent a function of their chemical composition, features of morphology and anatomy. Their variability is influenced by geological syngenetic and epigenetic processes that occur within the iron ore deposits of Kryvyi Rih basin. The latter is represented by nine deposits, which are exploited by five ore mining and enrichment works (GZKs). The Northern region of Kryvyi Rih basin includes Hannivske and Pervomayske deposits. The productive strata of both deposits consist of low-grade magnetite ores of the fifth and sixth ferruginous horizons. They are characterized by the authigenic-metamorphogenic mineralogical zonation. The purpose of the work is conditioned by the need for a detailed study of the laws of variability of chemical composition and physical properties of rock-forming minerals (magnetite and quartz), taking into account their position within zonal ore deposits. The study of the physical properties of rock-forming minerals was carried out according to standard methods using a microhardness tester, the chemical composition was investigated by segregating monomineral fractions of magnetite and quartz from ores of metamorphic or metasomatic origins of various mineral composition using a magnetic separator. The chemical analyzes were carried out in a standardized chemical laboratory. Statistical studies were performed using Excel software and Corel Draw. Result of the researches showed the nature of variability of the chemical composition, physical properties of magnetite and quartz in the sections of metamorphogenic and metasomatically altered ore strata of iron ore deposits. Practical significance is conditioned by the necessity of conducting detailed topomineralogical study of the productive strata of iron ore deposits of Kryvyi Rih basin in relation to the work on updating the mineralogical and technological map of the deposit, compiling an optimal scheme for ore blending in order to increase efficiency of the use of natural technological potential of magnetite quartzites on the basis of studying physical and chemical properties of the main rock-forming minerals of ferruginous quartzite.